A Simple Metabolic Flux Balance Analysis of Biomass and Bioethanol Production in Kluyveromyces Marxianus ATCC 26548 Batch Culture - Fahrurrazi Tompang, Mohamad; Abd Karim, Khairiah; Harun @Kamaruddin, Azlina; Syahidah Ku Ismail, Ku; ., .; ., . (International Journal of Engineering and Technology, 2018)
The role of a non-conventional yeast, Kluyveromyces marxianus in the bioprocessing industry has shown potential as metabolites producer, making it a suitable candidate for replacing the baker’s yeast for various industrial applications. The mathematical approach is used to analyze the flow of metabolites in the biological system in order to improve the desired product yield as well as the overall production process. Thus, the development of a simple model could lead to sustainability and practicability of the process. In this study, the comparative analysis of a simple metabolic network and a black box description is carried out in order to evaluate the growth and bioethanol production in K. marxianus batch culture. Metabolic flux balance methodology has shown to give a more accurate estimation with the complete analysis of the reaction rates. Furthermore, better evaluation of yeast behavior and performance in a batch system at varying glucose concentrations were achieved based on its stoichiometric reaction analysis. At the highest substrate concentration used, biomass growth was maximum at 12.32 g/l, with 7.75 g/L ethanol obtained. The biomass and bioethanol productions were mostly dependent on oxidative and reductive catabolism, respectively, in which the glucose and oxygen uptake rates played the main role in the regulation of the central metabolic networks. Therefore, biomass and ethanol production are strongly reliant on the cellular functionality of yeast in the culture, which shows the superiority of this method over the black box approach.
Keywords: Metabolic flux balance; Kluyveromyces marxianus; oxidative metabolism; reductive metabolism; oxygen uptake rate